EFEKTIVITAS MODEL COLABORATIVE PROBLEM SOLVING (CPS) DALAM MENINGKATKAN SELF CONCEPT SAINS MAHASISWA CALON GURU SEKOLAH DASAR - M. M. Talakua; J. Takaria (Pascasarjana IAIN Ambon, 2020)
Abstract: This study aims to determine the effectiveness of collaborative problem solving models in improving self-concept science student teachers at one LPTK SD State in the city of Ambon in Maluku. This study used a quasi-experimental with nonequivalent protest- posttest control group design, where the group will study measured self-concept science students using CPS models. The study population was a student at one LPTK PGSD in Maluku province, while the study sample were students PGSD VII semester of 2015/2016 academic year course on the development of elementary science education amounted to 30 students. Type of data analyzed in the study is quantitative data includes; Pretest-posttest self-concept and self-concept, and N-gain that has been converted using the MSI, and analyzed using descriptive statistics and inferential statistics. The results that the model of collaborative problem solving is very effective in improving self-concept science student teachers SD on one LPTK State in the city of Ambon, Maluku, both the results of Pre-SC and Post-SC obtained from the gain normalized or against each indicator self concept. Key words: model collaborative, problem solving, self concept sains